Dacnusa (Dacnusa) confinis Ruthe 1859 - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Supportive Care in Cancer, 2015)
Dacnusa ( Dacnusa ) confinis Ruthe, 1859 Distribution in Iran. Qazvin (Ghahari et al. 2011b; Khajeh et al. 2014). Distribution outside Iran. Widely distributed in Europe (Shenefelt 1974; Tobias 1986). Azerbaijan, Bulgaria, Denmark, Germany, Iceland, Ireland, Netherlands, Spain, Sweden and Switzerland (Yu et al. 2012), Czech Republic (Lozan et al. 2010; Yu et al. 2012), Greece (Papp 2007a; Yu et al. 2012), Hungary (Papp 2005b; Yu et al. 2012), United Kingdom (Griffiths 1967; Broad et al. 2012; Yu et al. 2012), Ukraine (Perepechayenko 2009). Host records. Chomatomyia syngenesiae Hardy, 1849, Liriomyza sp., Huidobrensis sp., Phytomyza glechomae Kaltenbach, 1862, and P. ranunculi Hendel, 1927 (Diptera: Agromyzidae) (Griffiths 1967; Yu et al. 2012). Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on page 20, DOI:10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961